Impact of hate speech in digital media on pre-election public opinion - Alfian Nurochman; Ridho Al-Hamdi; Suswanta (Jurnal Studi Komunikasi, 2024)
This research investigates the influence of social media on public opinion in Indonesia, with a focus on the 2024 general election. As of January 2023, Indonesia has 167 million active social media users or 60.4% of the total population. This study highlights how platforms such as Twitter can spread hate speech, causing social tension, psychological distress, and even physical violence, especially against minority groups. This rapid spread of misinformation and hate speech threatens the democratic process, impacting voter behaviour and trust in institutions. Using a qualitative case study approach, this research explores user experiences, identifying forms of hate speech such as defamation and incitement. The findings emphasise the need for stricter law enforcement, public education on tolerance, and ethical political campaigns. While social media enhances political engagement, it requires robust measures to prevent abuse and ensure election integrity and social cohesion.